Precision Medicine in Africa: Promises and Opportunities (Springer Nature, 2025)
The relevance of genomic medicine embodies using an individual's genomics and molecular genetic information to personalize treatment and predict drug response to ensure safer and more cost-effective therapies. An African framework for implementing genomic medicine was recently developed to highlight the elements required within the African context and provide some recommendations on how African countries can work on putting them in place by building on existing infrastructure. These measures would enable resource-limited countries to implement appropriate genomics-based health-related interventions, drawing on experiences from elsewhere but adapting to the African context where necessary. In developing the framework, the existing genomic medicine activities in Africa were investigated. This book aims to describe the current status of precision medicine and discuss the clinical studies related to precision medicine that have been conducted on African populations to improve healthcarein Africa. This book comprises three sections: infectious diseases, non-communicable diseases, and bioinformatics tools and resources. Each section is covered in several chapters, each dealing with a specific disease or group of diseases together with the necessary formalism. Based on existing literature, the collection summarizes Africa's state of the art of genomics and precision medicine activities. The book is helpful for researchers, clinicians, and policymakers; the secondary audience is students, funders, and healthcare staff. This is an open access book.